Demand for money in selected developed and developing countries does economic uncertainty matter (IR) - Lim, Siew Yong (2015)
The purpose of this research is to investigate the relationship between the demand for money (namely, narrow money demand and broad money demand) and optimal economic uncertainty index; in addition to the optimal economic uncertainty index, two control variables are included in the money demand function, namely exchange rate and inflation; note that the optimal economic uncertainty index is a summary information of economic uncertainty for the future state of the economy. The optimal economic uncertainty index applies in this research is an optimal algorithm approach. The relationships between the demand for money and the optimal economic uncertainty index, the real exchange rate, the real income, the real interest rate and the inflation are examined by using the autoregressive distributed lag (ARDL) dynamic heterogeneous panel cointegration test. Four selected developed countries and five selected developing countries are taken up as samples in this research. Using the panel cointegration method, the findings provide some policy implications; the optimal economic uncertainty index can serve as a signaling indicator of uncertainty about future economic events to promote the stability of money demand function (namely, narrow money demand function and broad money demand function), and the exchange rate and inflation are useful indicators of central banks decision making process that eventually enhance the control of monetary aggregates in the transmission of monetary policy.